2006
DOI: 10.1785/0120050056
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Time-Domain, Variable-Period Surface-Wave Magnitude Measurement Procedure for Application at Regional and Teleseismic Distances, Part II: Application and Ms-mb Performance

Abstract: The Russell surface-wave magnitude formula, developed in Part I of this two-part article, and the M s (VMAX) measurement technique, discussed in this article, provide a new method for estimating variable-period surface-wave magnitudes at regional and teleseismic distances. The M s (VMAX) measurement method consists of applying Butterworth bandpass filters to data at center periods between 8 and 25 sec. The filters are designed to help remove the effects of nondispersed Airy phases at regional and teleseismic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Therefore, M w is actually acting as a surrogate for a rapid change in material properties occurring near the water table encountered by larger and more deeply buried explosions. The apparent differences in compression to shear energy scaling for explosions and earthquakes are also observed in published (and widely used) developments of the m b versus M s discriminant (see Stevens and Day, 1985;Taylor, 1996;Bonner et al, 2006). The apparent correlation between Z and M w is fundamentally due to sampling bias for the explosion population-there are no large shallow explosions and no small deep explosions in this data set.…”
Section: Nts Data Analysis With the Mdac Multistation Discriminantsupporting
confidence: 61%
“…Therefore, M w is actually acting as a surrogate for a rapid change in material properties occurring near the water table encountered by larger and more deeply buried explosions. The apparent differences in compression to shear energy scaling for explosions and earthquakes are also observed in published (and widely used) developments of the m b versus M s discriminant (see Stevens and Day, 1985;Taylor, 1996;Bonner et al, 2006). The apparent correlation between Z and M w is fundamentally due to sampling bias for the explosion population-there are no large shallow explosions and no small deep explosions in this data set.…”
Section: Nts Data Analysis With the Mdac Multistation Discriminantsupporting
confidence: 61%
“…We compared our magnitude to previous M s ∶m b research (Bonner, Pasyanos, et al, 2006;Bonner, Russell, et al, 2006) for Eurasia and found the NK event plots slightly above the Murphy et al (1997) event screening value, which is M s 2:90 for an IDC m b of 4.1 (Fig. 3).…”
Section: Magnitude Estimationmentioning
confidence: 61%
“…We do note that some mining explosions do not discriminate well because of the reduced P-wave amplitudes associated with delay-firing practices (Bonner, Pasyanos, et al, 2006). Some have suggested the NK results could be evidence of a convergence of the earthquake and explosion M s ∶m b populations at small magnitudes (as postulated in Stevens and Day [1985]); however, Bonner, Russell, et al (2006) saw no evidence of the convergence at the Nevada Test Site (NTS) for events of similar and smaller m b . Others have suggested this is further evidence of the need to revise the current screening criteria used for earthquake and explosion identification.…”
Section: Magnitude Estimationmentioning
confidence: 98%
See 2 more Smart Citations